Trends and prediction of extreme precipitation indices in three cities of Burkina Faso using non-parametric statistics and the Holt-Winters smoothing method - Joseph Yaméogo (Institute of Meteorology and Water Management – National Research Institute Podlesna 61, 2025)
Climate extremes have become increasingly important in recent years, leading to renewed scientific interest. However, few studies have focused on precipitation extremes in cities in Burkina Faso, a Sahelian country in West Africa. The aim of this study is to analyze trends and to project future extreme precipitation indices in three cities in Burkina Faso. To this end, precipitation data, recorded daily, were collected from the National Meteorological Agency of Burkina Faso (NMABF) over the period 1991-2020. The stations selected were Boromo for the small town of Boromo, Saria for the medium-sized town of Koudougou, and Bobo-Dioulasso for the town of Bobo-Dioulasso. The precipitation data were used to calculate the extreme precipitation indices described by ETCCDMI (Expert Team for Climate Change Detection Monitoring and Indices) using Rclimdex. Descriptive statistics, the Mann-Kendall test, and trends from innovative models were used to analyze the extreme precipitation indices; the Holt-Winters additive model was used to analyze future projections. The study showed considerable variability and a monotonic increasing trend in extreme precipitation indices over the period 1991-2020. However, for the city of Koudougou, the trend was a non-monotonic increase. The forecast based on the Holt-Winters additive model shows considerable variability in the extreme precipitation indices, with an upward trend over the period 2020-2030. On the other hand, in the city of Koudougou, indices of precipitation duration will decrease, indicating that the city will be affected most by the frequency and intensity of extreme precipitation.